Transformation of university language education in the context of artificial intelligence integration - Вракіна, Вікторія Вікторівна; Танько, Євгенія Владиславівна; Беркутова, Тетяна Іванівна (BoScience Publisher, 2026)
The article provides an analytical overview of the transformation of university language education in the context of artificial intelligence integration. It examines the didactic potential of AI-based tools and outlines key directions for their use in teaching foreign languages in higher education. Particular attention is paid to the possibilities of personalized learning, immediate feedback, expanded opportunities for language practice, and support for teachers’ professional activities. The paper analyzes widely used artificial intelligence tools, including chatbots, online language-learning platforms and intelligent content-generation applications. Special emphasis is placed on the pedagogical potential of chatbots, with ChatGPT discussed as an example in the development of students’ foreign language communicative competence. Alongside the advantages, the article identifies major limitations and risks associated with the use of artificial intelligence, including issues of academic integrity, ethical and legal concerns, data protection, and digital inequality. The study concludes that artificial intelligence should be regarded as a tool that contributes to the transformation of language education and expands the pedagogical capabilities of instructors, while not replacing their central role in the teaching and learning process.
Keywords: artificial intelligence; language education; higher education; digital technologies; chatbots; educational transformation